Coral-Derived Endophytic Fungal Product, Butyrolactone-I, Alleviates Lps Induced Intestinal Epithelial Cell Inflammatory Response Through TLR4/NF-κB and MAPK Signaling Pathways: An in vitro and in vivo Studies - Chen, Shengwei; Zhang, Yi; Niu, Xueting; Mohyuddin, Sahar Ghulam; Wen, Jiayin; Bao, Minglong; Yu, Tianyue; Wu, Lianyun; Hu, Canyin; Yong, Yanhong; Liu, Xiaoxi; Abd El-Aty, A. M.; et al. (Frontiers in Nutrition, 2021)
Herein, we assessed the anti-inflammatory and intestinal barrier protective effects of butyrolactone-I (BTL-1), derived from the coral-derived endophytic fungus (Aspergillus terreus), using the LPS-induced IPEC-J2 inflammation model and the DSS-induced IBD model in mice. In IPEC-J2 cells, pretreatment with BTL-I significantly inhibited TLR4/NF-κB signaling pathway and JNK phosphorylation, resulting in the decrease of IL-1β and IL-6 expression. Interestingly, BTL-1 pretreatment activated the phosphorylation of ERK and P38, which significantly enhanced the expression of TNF-α. Meanwhile, BTL-1 pretreatment upregulated tight junction protein expression (ZO-1, occludin, and claudin-1) and maintained intestinal barrier and intestinal permeability integrity. In mice, BTL-1 significantly alleviated the intestinal inflammatory response induced by DSS, inhibited TLR4/NF-κB signaling pathway, and MAPK signaling pathway, thus reducing the production of IL-1, IL-6, and TNF-α. Further, the expression of tight junction proteins (ZO-1, occludin, and claudin-1) was upregulated in BTL-1 administrated mice. Therefore, it has been suggested that butyrolactone-I alleviates inflammatory responses in LPS-stimulated IPEC-J2 and DSS-induced murine colitis by TLR4/NF-κB and MAPK signal pathway. Thereby, BTL-1 might potentially be used as an ocean drug to prevent intestinal bowel disease.